2021
DOI: 10.1042/bsr20203145
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between tumor-associated macrophage infiltration and progression in cervical carcinoma

Abstract: Tumor microenvironment (TME) plays a particularly important role in the progression, invasion and metastasis of cervical carcinoma (CC). Tumor-associated macrophages (TAMs) are significant components of the tumor microenvironment in CC. However, the results of studies on the correlation between TAMs and progression in CC are still controversial. This research aimed to investigate the relationship between TAMs infiltration and progression in CC. A total of 100 patients with CC were included in the study. The co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…A high density of CD68+TAMs is associated with lymph node metastasis. 26 Under normal circumstances, dendritic cells promote the antitumor immune response of Th1/CTL and enhance the immune monitoring of tumor cells by secreting IL‐12. Studies have confirmed that an HPV16E5 protein‐targeted dendrite vaccine used in the treatment of tumor mice, controlled the growth of mouse tumors and improved the survival rate of mice.…”
Section: Discussionmentioning
confidence: 99%
“…A high density of CD68+TAMs is associated with lymph node metastasis. 26 Under normal circumstances, dendritic cells promote the antitumor immune response of Th1/CTL and enhance the immune monitoring of tumor cells by secreting IL‐12. Studies have confirmed that an HPV16E5 protein‐targeted dendrite vaccine used in the treatment of tumor mice, controlled the growth of mouse tumors and improved the survival rate of mice.…”
Section: Discussionmentioning
confidence: 99%
“…In Ovestad's study, CD160 was also downregulated in the CIN3/AIS lesions (45). The CD68 tumor-associated macrophages in CESC were significantly increased than those in normal tissue or paracarcinoma, and high stromal CD68 tumor-associated macrophages were born on lymph node metastasis (46). The upregulation of FUCA1 in SiHa is shown in Kalliopi's study (47).…”
Section: Discussionmentioning
confidence: 87%
“…According to some studies, the number of macrophages increases with the progression of cervical neoplastic lesions [16,18,[20][21][22][23][24]. Tumor cells have been suggested to secrete various types of cytokines into the TME to promote monocyte migration to the neoplastic tissue.…”
Section: Discussionmentioning
confidence: 99%